2005
DOI: 10.1158/0008-5472.can-05-0450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Aberrantly Spliced Form of HDMX in Human Tumors: A New Mechanism for HDM2 Stabilization

Abstract: The HDMX protein is closely related to HDM2 with which it shares different structural domains, particularly the p53 binding domain and the ring finger domain, where the two HDM proteins interact. Several oncogenic forms derived from splicing of HDM2 have been described in cancer. This work aimed at investigating whether analogous forms of HDMX exist in human tumors. Here, we report the characterization of an aberrantly spliced form of HDMX, HDMX211, isolated from the thyroid tumor cell line, ARO. HDMX211 binds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 35 publications
1
52
0
1
Order By: Relevance
“…HDMX211 binds and stabilizes HDM2 and also counteracts HDM2-mediated p53 degradation. 22 Interestingly, Western blot analysis of one of three ALL cases showed the presence of an additional band at B30 kDa, suggesting that some pre-B ALL cases have both HDM4 and HDM4-S forms. The antibody against HDM4 and primers for RT-PCR used in this study will not detect the protein or mRNA of the HDMX211 variant according to the reported sequence.…”
Section: Discussionmentioning
confidence: 94%
“…HDMX211 binds and stabilizes HDM2 and also counteracts HDM2-mediated p53 degradation. 22 Interestingly, Western blot analysis of one of three ALL cases showed the presence of an additional band at B30 kDa, suggesting that some pre-B ALL cases have both HDM4 and HDM4-S forms. The antibody against HDM4 and primers for RT-PCR used in this study will not detect the protein or mRNA of the HDMX211 variant according to the reported sequence.…”
Section: Discussionmentioning
confidence: 94%
“…29 HDM-A lacks exon 9 sequences encoding the acidic domain and, as a result, cannot stabilize HDM2 and is susceptible to HDM2-initiated degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Probably the high expression level of DDX39 in the lymphoid tissues exceeds the capacity of splicing machinery to regulate the accurate splicing pattern, 27 thereby generating DDX39-SS. The biological significance of the COOH terminally truncated variants of DDX39, DDX39-S and -SS, is unclear but they could take part in tumor development in some way 28 because DDX39 may form a dimer structure using the NH 2 terminal domain, as inferred from the crystal structure of UAP56. 29 Since among the three variants, DDX39-L is the only transcript likely overexpressed in LSCC and preserves all the motifs necessary for RNA helicase activity, we examined recombinant DDX39-L produced in the baculoviral system for RNA helicase-related activities.…”
Section: Discussionmentioning
confidence: 99%